Evaluasi Program Sertifikasi Guru TK dalam Peningkatan Mutu Pendidikan Anak Usia Dini - Nurlaili Hidayati; Zohra Fatimah (Primary Journal of Multidisciplinary Research, 2026)
The Kindergarten (TK) teacher certification program is one of the government’s strategic policies aimed at enhancing teacher professionalism and improving the quality of early childhood education services. Certification not only serves as formal recognition of professional competence, but is also expected to promote improvements in the quality of the learning process, foster teachers’ creativity, and strengthen their role as facilitators of children’s holistic development. This study aims to evaluate the effectiveness of the kindergarten teacher certification program in improving teachers’ pedagogical, professional, social, and personal competencies, as well as its impact on the quality of classroom learning. This research employs a qualitative approach with a descriptive evaluative design. Data were collected through in-depth interviews with certified kindergarten teachers, school principals, and early childhood education supervisors, complemented by observations of classroom learning processes and documentation studies of teaching materials. Data were analyzed thematically to identify changes in teacher competencies before and after certification, as well as challenges encountered in its implementation. The findings indicate that certification contributes positively to improving curriculum understanding, more systematic lesson planning, the use of creative learning media, and increased teacher confidence and work motivation. In addition, there are indications of improved teacher–child interactions, which have a positive impact on students’ cognitive and socio-emotional development. However, this study also identifies several challenges, including limited post-certification continuous professional development programs, suboptimal academic supervision, and a tendency among some teachers to perceive certification primarily as an administrative requirement rather than as a process of ongoing competency improvement. Therefore, strengthening professional mentoring policies, providing advanced training relevant to the needs of kindergarten teachers, and implementing a sustainable evaluation system are necessary to ensure that the certification program truly generates a significant and lasting impact on the comprehensive and sustainable quality of early childhood education.